2018
DOI: 10.1139/cjc-2017-0472
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots based dual-emission silica nanoparticles as ratiometric fluorescent probe for chromium speciation analysis in water samples

Abstract: A simple and effective strategy for designing a ratiometric fluorescent nanosensor was described. A carbon dots (CDs) based dual-emission nanosensor for chromium speciation analysis was developed by coating CDs on the surface of dye-doped silica nanoparticles. The fluorescence of the resulting dual-emission silica nanoparticles was quenched in acetic acid through potassium bromate (KBrO3) oxidation. Cr(VI) was able to catalyze KBrO3 oxidation, resulting in ratiometric fluorescence accelerated quenching respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Besides, it has been shown that silica gel glasses produced from silicate carboxylate precursors exhibit high PL characteristics [13]. Recent advancements in synthesis and analysis of silica/CDs composites revealed great potential of such systems in bioimaging, sensor, as well as solid-state lighting applications, and depending on the synthesis methods and the precursors used, it is possible already to achieve the PL QY from typically 7-14 up to 60% [14][15][16][17][18][19][20][21][22]. Table 2 gives the PL characteristics of some carbon-containing silica-based materials synthesized using various methods.…”
Section: -4mentioning
confidence: 99%
“…Besides, it has been shown that silica gel glasses produced from silicate carboxylate precursors exhibit high PL characteristics [13]. Recent advancements in synthesis and analysis of silica/CDs composites revealed great potential of such systems in bioimaging, sensor, as well as solid-state lighting applications, and depending on the synthesis methods and the precursors used, it is possible already to achieve the PL QY from typically 7-14 up to 60% [14][15][16][17][18][19][20][21][22]. Table 2 gives the PL characteristics of some carbon-containing silica-based materials synthesized using various methods.…”
Section: -4mentioning
confidence: 99%
“… 18 Results showed that the addition of Cu 2+ ion could bring about obvious ratiometric fluorescence response owing to the recognition interaction from the terminal ethylenediamine groups on CDs surface. In Xiang's research works, 19,20 they found that this dual-emission nanosystem based on CDs linked silica nanoparticles could be used to build another ratiometric fluorescence sensor through the inhibition or catalyzing the oxidation process of KBrO 3 . In addition, with the help of the dispersion and crosslinking capabilities of silica layer, Liu et al obtained dual-emission nanocomposite with apparent core–shell structure via covering CDs to the external surface of nitride phosphor.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, a promising direction is the formation of CDs with doped heteroatoms on the surface of oxide materials, in particular silica. Thus, recent advancements in synthesis and analysis of silica/CDs composites revealed great potential of such systems in bioimaging, sensor, as well as solid-state lightning applications, and, depending on the synthesis methods and the precursors used, it is possible already to achieve the PL QY from typically 5-14 up to 41 % [13][14][15][16][17][18][19][20]. Most of the synthetic methods are still relatively complex and costly.…”
Section: Introductionmentioning
confidence: 99%